Assistive Technology for Literacy in Students With Physical Disabilities: A Systematic Review. Issue 4 (December 2019) - Stauter, Donna W.; Prehn, Judy; Peters, Megan; Jeffries, Lynn M.; Sylvester, Lorraine; Wang, Hongwu; Dionne, Carol
The purpose of this study was to systematically review literature on assistive technology (AT) used to develop literacy skills in students with physical disabilities. Primary databases were searched using search terms AT, disability, and literacy. Eight studies were eligible for inclusion. Six studies reported positive change to literacy components with AT support, and two reported a statistically significant change. Evidence offers support for AT in developing reading skills in this population. Future research could include reliable outcome measures, a classification system for participants' disabilities, increased rigor of research design, and statistical data analysis.